Activation of Sirt1/PGC1α pathway attenuates neuroinflammation injury in Parkinson's disease. (2nd January 2022) - Yang, Yang; Gong, Zhongying; Wang, Zhiyun; Lu, Yi
Abstract: Parkinson's disease is a brain disorder that is featured by shaking palsy, which affect the motor system. The pathogenesis of Parkinson's disease has been ascribed to neurodegenerative disorder, neural oxidative stress, neuroinflammation, and neurotransmitter disorder. In the present study, we explored the influence of Sirt1/PGC1α pathway in regulating BV-2 cells viability under TNFα treatment. Our results demonstrated that the activity of Sirt1/PGC1α pathway was significantly downregulated in response to TNFα treatment. Reactivation of Sirt1/PGC1α pathway through supplementation of SRT1720 significantly elevated the viability of BV-2 cells under an in vitro neuroinflammation model. Therefore, our results report a novel signaling pathway responsible for the survival of neuron under neuroinflammation. Re-activation of Sirt1/PGC1α pathway may be a potential therapeutic approach for the treatment of Parkinson's disease through enhancing neuronal viability.